Modelling of variable‐speed refrigeration for fast‐frequency control in low‐inertia systems. Issue 6 (19th December 2020) - Vorwerk, Johanna; Markovic, Uros; Aristidou, Petros; Vrettos, Evangelos; Hug, Gabriela
Abstract : In modern power systems, shiftable loads contribute to the flexibility needed to increase robustness and ensure security. Thermal loads are among the most promising candidates for providing such service due to the large thermal storage time constants. This study demonstrates the use of variable‐speed refrigeration (VSR) technology, based on brushless DC motors, for the fast‐frequency response. First, the authors derive a detailed dynamic model of a single‐phase VSR unit suitable for time‐domain and small‐signal stability analysis in low‐inertia systems. For analysing dynamic interactions with the grid, they consider the aggregated response of multiple devices. However, the high computational cost involved in analysing large‐scale systems leads to the need for reduced‐order models. Thus, a set of reduced‐order models is derived through transfer function fitting of data obtained from time‐domain simulations of the detailed model. The modelling requirements and the accuracy versus computational complexity trade‐off are discussed. Finally, the time‐domain performance and frequency‐domain analyses reveal substantial equivalence between the full‐ and suitable reduced‐order models, allowing the application of simplified models in large‐scale system studies.